Performance of Prediction Interval Estimators based on Random Forest Models with Correlated Predictors - Ilma, Meisyatul; Sartono, Bagus; Wijayanto, Hari (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
Uncertainty in prediction results is a crucial aspect that needs to be taken into account in regression modeling, especially when there is a high correlation between explanatory variables. This study aims to evaluate the performance of three prediction interval formation approaches, namely Out-of-Bag Prediction Interval (OOB-PI), Quan tile Regression Forest (QRF), and Split Conformal Prediction (SC), in Random Forest modeling. The evaluation was conducted through a simulation study with a variety of data structures, including the level of correlation between variables, the shape of the mean function, and the type of error distribution. Further validation was conducted using data from the National Socio-Economic Survey (SUSENAS) of West Java Province in 2023. The results show that increasing the correlation between explanatory variables can improve the efficiency and accuracy of prediction interval estimation. Overall, OOB-PI showed the most balanced performance compared to the other two methods, with a prediction coverage rate close to 90% and a narrower interval width than QRF and SC. This finding indicates that OOB-PI is an adaptive and efficient approach for various data structures, including socioeconomic data with highly correlated predictors.